The use of musculotendinous stretch-shortening cycle: A comparison between young and elite sprinters during the first step of the acceleration phase - Aeles, J.; Jonkers, I.; Debaere, S.; Delecluse, C.; Vanwanseele, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
This study aimed to determine the differences between elite and young sprinters in the use of a stretch-shortening cycle (SSC) at the ankle, knee and hip joint by analysing muscle-tendon (MT) lengths during the first stance after block clearance (start acceleration phase). Sixteen elite athletes (8 male and 8 female) and twenty-six young athletes (16 male and 10 female) performed an explosive start action. Twelve MX3 cameras (250Hz) and two Kistler force plates (1000 Hz) were used to collect 3D marker and ground reaction forces (Nexus, Vicon). A musculoskeletal model (Hamner, Seth, & Delp; 2010) was scaled to each subject`s individual anthropometry. An inverse kinematics procedure was conducted to obtain joint angles and individual MT lengths of ankle plantar flexors, knee extensors, glutei and hamstring muscles were computed. These results were normalised by subtracting MT lengths during the static pose (l0). For each muscle, stance phase was divided into a MT lengthening and a shortening phase. MT length change, the time interval (Ät) and the rate of deformation (lmax-lmin/Ät) were calculated per phase. The use of a stretch-shortening cycle during stance was seen in the gastrocnemius, soleus and rectus femoris muscle. MT shortening was higher in the elite group compared to the youth athletes in both gastrocnemius` heads (33.2 mm ± 4.5 (med); 34.0 mm ± 4.5 (lat) vs. 26.7 mm ± 7.6; 27.3 mm ± 7.7 respectively) and the soleus muscle (45.4 mm ± 5.1 vs. 37.9 mm ± 7.7 respectively). Shortening rate was 23.2% larger in the elite group for the soleus muscle. During MT elongation in the rectus femoris, Ät was less in the elite group (85 ms ± 24 vs. 105 ms ± 32) while MT shortening was larger in the elite group (19.2 mm ± 3.8) compared to the youth athletes (14.9 mm ± 6.7). These results give strong evidence that the presence of SSC mechanisms during the first stance in the acceleration phase is dependent on individual muscles. In a future project we will look at the contribution of the tendon to joint power and performance in sprinters.